2015
DOI: 10.48550/arxiv.1502.02290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How Hard is Computing Parity with Noisy Communications?

Chinmoy Dutta,
Yashodhan Kanoria,
D. Manjunath
et al.

Abstract: We show a tight lower bound of Ω(N log log N ) on the number of transmissions required to compute the parity of N input bits with constant error in a noisy communication network of N randomly placed sensors, each having one input bit and communicating with others using local transmissions with power near the connectivity threshold. This result settles the lower bound question left open by Ying, Srikant and Dullerud (WiOpt 06), who showed how the sum of all the N bits can be computed using O(N log log N ) trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…We then use our technique to derive the main result of this paper -a lower bound for wireless sensor networks. This simplifies and extends a lower bound of [DKmR08,DKmR15] for this model. A wireless sensor network consists of sensors that collect and cooperatively process data in order to compute some global function.…”
Section: Introductionsupporting
confidence: 68%
See 4 more Smart Citations
“…We then use our technique to derive the main result of this paper -a lower bound for wireless sensor networks. This simplifies and extends a lower bound of [DKmR08,DKmR15] for this model. A wireless sensor network consists of sensors that collect and cooperatively process data in order to compute some global function.…”
Section: Introductionsupporting
confidence: 68%
“…It was shown by Dutta, Kanoria, Manjunath and Radhakrishnan [DKmR08,DKmR15], that computing the parity of the inputs requires Ω(n log log n) transmissions. This result showed that the protocol presented by Ying, Srikant and Dullerud [YSD06] for computing the sum of all the bits (and hence any symmetric functions of these bits) is optimal.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations